(untitled) (Applied Biological Research, 2014)
The present study was conducted during 3 consecutive years (2009-2010 to 2011-12) at Horticultural Research Station, Lam, Andhra Pradesh (India) to evaluate ten promising and diverse genotypes of coriander (Coriandrum sativum L.) procured from different states of India. Maximum yield was achieved in genotype LCC-237 (959.0 kg ha-1) followed by LCC-236 (897 kg ha-1) which were on par with each other but significantly superior over check variety Sudha (723 kg ha-1). Considering the stability parameters for yield, genotypes RKD-13 and LCC-236 with almost unit regression (-0.90 and 1.12, respectively) may be considered as stable genotypes. The genotype LCC-236 with significant deviation in regression coefficient may be considered as plastic genotype that outperformed other genotypes including best check (Sudha) in all the seasons tested. The mean performance of genotype RKD-13 was significantly lower than check Sudha, hence considered as a poor yielder. Early flowering and maturity, coupled with superiority in these traits, when correlated with yield was found to be the reason for better performance of genotype LCC-236 under diverse environmental conditions. This genotype also possessed high essential oil content than other genotypes evaluated.